The Influence of Website Design, E-Trust, and E-Service Quality on Online Purchase Decision - Hetty Sri Haryanti (Soegijapranata Catholic University, 2024)
The purpose of this research is to analyze the influence of website design, e-trust and e-service quality either partially or simultaneously to purchase decision. The sample was 86 customers of the coffee shop Janji Jiwa at Tembalang Semarang. The analysis techniques used were multiple linear regression with least squares equation, the coefficient of determination, and t-statistics and F statistics for testing the hypotheses partially and simultaneously using 5% level of significance. The results indicate that website design, e-trust, and e-service quality have a significant effect on online purchase decisions either partially or simultaneously.